Grammatical Errors of Indonesian-English Text Translation in The Second Semester Student of Arabic Study Program at FTIK IAIN Pontianak - Nanik Shobikah (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2019)
This article aims to investigate some grammatical errors made by Arabic students in translating Indonesian text to English text. In translating, the students must be aware of the grammar rules to avoid some mistakes. The mistakes or errors in grammar can influence the idea of message delivery. Grammatical errors should be corrected directly to avoid misunderstanding. The research problem formulated by the researcher is (a) what types of grammatical errors made by the second semester students of Arabic study program of Teacher Training and Education Faculty of Pontianak State Islamic Studies?; and (b) What are the highest and lowest percentage of grammatical error in translated texts made by the students?. This study aims to uncover and identify the grammatical errors found in translation made by the students and describe the percentage of each type of grammatical errors in translated texts made by the students. This study uses qualitative descriptive method. The subject of this study is 31 Arabic study program students of Teacher Training and Education Faculty of Pontianak State Islamic Studies. This study takes in the second semester of Arabic study program year 2018-2019 in English For Specific Purpose (ESP) subject. In this subject, the students learned how to translate Indonesian-English and English-Indonesian texts. Data collection used in this research are documentation in the form of written test and observation during the test. The result showed the types of errors made the students are errors in the use of verb, noun phrase, pronoun, adjective phrase and preposition. From the finding, it can be seen that the highest error is in the use of verb form (32,23%), then it followed by the use of noun phrase (24,16%), the use of pronoun (16,13%), the use of adjective phrase (14,52%), and the use of preposition (12,90%) as the lowest error